Escherichia coli positive infratentorial subdural empyema secondary to mastoiditis and underlying cholesteatoma. (28th April 2014) - Mirza, Omar; Varadarajan, Vinay; Youshani, Amir Saam; Willatt, David J
Abstract : Infratentorial subdural empyema is a neurosurgical emergency that is associated with an alarmingly high morbidity and mortality if appropriate management is delayed. It is an important differential to consider when confronted with a patient with a reduced Glasgow Coma Scale, focal neurology and symptoms of raised intracranial pressure in the presence of a head and neck infection. It is also important that the primary team managing these patients is aware of the many pathogens that may be involved, including Escherichia coli. Early recognition, prompt diagnosis, timely involvement of the appropriate multidisciplinary teams, including neurosurgery, otorhinolaryngology, radiology and microbiology should be sought, and urgent intervention are imperative in avoiding a fatal outcome. This article presents a case of E coli- positive infratentorial subdural empyema secondary to mastoiditis due to underlying cholesteatoma, and a review of the pertinent literature.